Gene loss, thermogenesis, and the origin of birds. (3rd April 2013) - Newman, Stuart A.; Mezentseva, Nadezhda V.; Badyaev, Alexander V.
Abstract : Compared to related taxa, birds have exceptionally enlarged and diversified skeletal muscles, features that are closely associated with skeletal diversification and are commonly explained by a diversity of avian ecological niches and locomotion types. The thermogenic muscle hypothesis (TMH) for the origin of birds proposes that such muscle hyperplasia and the associated skeletal innovations are instead the consequence of the avian clade originating from an ancestral population that underwent several successive episodes of loss of genes associated with thermogenesis, myogenesis, and skeletogenesis. Direct bird ancestors met this challenge with a combination of behavioral strategies (e.g., brooding of nestlings) and acquisition of a variety of adaptations for enhanced nonshivering thermogenesis in skeletal muscle. The latter include specific biochemical alterations promoting muscle heat generation and dramatic expansion of thigh and breast muscle mass. The TMH proposes that such muscle hyperplasia facilitated bipedality, freeing upper limbs for new functions (e.g., flight, swimming), and, by altering the mechanical environment of embryonic development, generated skeletal novelties, sometimes abruptly, that became distinctive features of the avian body plan.